Meios alternativos de transporte como estratégia de melhoria da mobilidade urbana no município de Aracaju - Nascimento, Matheus Paixão Bezerra (2017)
The present study aimed to verify the current situation of urban mobility in the city of Aracaju and to propose improvements for it, focusing on the promotion of means of transportation alternative to the use of the private car. In the present study we used documentary research, application of a questionnaire to collect data. The results showed that, in the city of Aracaju, people tend to use the private car in commuting to daily appointments. The data collected also allowed us to verify that the higher income level increases the tendency to use the car as a regular and predominant means of transportation. The research public has shown concern about the lack of public safety and that they seek comfort, speed and security that other modes supposedly do not offer. Based on the information obtained, the study concluded that the city of Aracaju has problems of urban mobility, but with the potential to provide more efficient displacements to its population through the strengthening of alternative transportation means, but it lacks governmental actions regarding infrastructure, security and educational or promotional actions that, together, aim at changing the behavior of the population.